1998
DOI: 10.1002/(sici)1097-4555(199804)29:4<245::aid-jrs220>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Study of thecis andtrans conformers of 2-halophenols using coherent anti-Stokes Raman spectroscopic and quantum chemical methods

Abstract: The OH stretching wavenumbers of the cis and trans conformers of 2-halophenols were studied in the gas phase by using coherent anti-Stokes Raman spectroscopy and quantum chemical calculations. The wavenumber di †erences between the two isomers of 2-Ñuoro-, 2-chloro-and 2-bromophenol were found to be 20, 71 and 102 cm-1, respectively. These results are in good agreement with quantum chemical calculations based on the use of the density function theory. However, the calculated energy di †erences between two isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
5
16
0
Order By: Relevance
“…In 2‐bromophenol ( 23 e ), there exist two isomers ( cis and trans ) originating from the orientation of the OH group with respect to the Br substituent (see Figure ). Our results at the PBE‐D/TZ2P level corroborate the greater stability of the cis over the trans form, in agreement with the results reported in the literature . According to the calculations, these two forms are close in energy in the gas phase (Δ E =3.7 kcal mol −1 ) and solvent, for example, in chloroform solution when using the COSMO model, has only a small effect on the energy gap (Δ E =2.0 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2‐bromophenol ( 23 e ), there exist two isomers ( cis and trans ) originating from the orientation of the OH group with respect to the Br substituent (see Figure ). Our results at the PBE‐D/TZ2P level corroborate the greater stability of the cis over the trans form, in agreement with the results reported in the literature . According to the calculations, these two forms are close in energy in the gas phase (Δ E =3.7 kcal mol −1 ) and solvent, for example, in chloroform solution when using the COSMO model, has only a small effect on the energy gap (Δ E =2.0 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 2-bromophenol (figure 2) is the most stable isomer, suggesting an effect of stabilization when the bromine atom is in the ortho position of the phenolic ring, as a result of the interaction between the bromine and the hydrogen atom of the hydroxyl group. The formation of a hydrogen bond has been previously reported for 2-bromophenol based on results from Raman spectroscopic and far-infrared experiments [11,12]. Hence, for molecules where the bromine atom and the hydroxyl group are attached in ortho position in the benzene ring, the Cox scheme must be applied with some caution, since the stabilizing interactions between these two substituents are totally neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly the ortho halophenols have been the subject of numerous experimental [10][11][12][13][14][15][16][17] and theoretical [10,[18][19][20] studies focused on the bond strength, geometry, and stabilization energy induced by hydrogen bonding. Considering 2-bromophenol it has been shown in previous works that its molecular structure is planar, and the most stable conformation is that where the hydroxyl group adopts a cis configuration relatively to the bromine atom in 2-position, yielding the formation of a halogen-hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…intramolecular hydrogen bonding may occur. This hydrogen bond has been observed for the 2-bromophenol in the earlier studies based on results from Raman spectroscopic and far-infrared experiments [57,58], and also in the previous work devoted to the thermochemistry of the monobromophenol isomers [5]. In that study, it was suggested that for molecules where the bromine atom and the hydroxyl group are attached in the ortho-position in the benzene ring, the Cox Scheme should be applied with some caution, due to the presence of stabilizing interactions between these two substituents, which are totally neglected in the Cox Scheme and so the large differences of the Cox estimates in the case of the 2,4-and 2,6-dibromophenol.…”
Section: Discussionmentioning
confidence: 99%